Studies on bile salt deconjugation following small bowel bypass procedures. - Wise, L (1975)
Using the glycine-l-14C-cholic acid (14C-GCA) test, bile salt deconjugation and excretion were studied in 26 subjects with morbid exogenous obesity before and at selected intervals after jejuno-ileal bypass. In the preoperative group there was no malabsorption or intestinal bacterial deconjugation of the bile salts. In the immediate postoperative period (with relative sterilization of the bowel) there was only a trace of 14C in the breath, but the fecal 14C was highly elevated, indicating severe malabsorption without bacterial activity. In the 8 to 10 day postoperative period both the breath and fecal 14C content were highly elevated, indicating malabsorption and normal bacterial activity. Five to 8 months postoperatively both the breath and fecal 14C content showed only moderate elevation, indicating adaptation. It is suggested that the 14C-GCA test is useful in evaluating the adequacy of small bowel bypass procedures and also in following the adaptive response after the bypass. A significant increase in the breath and fecal 14C soon after surgery followed by rapid decrease suggests an adequate bypass and unusually fast adaptation. If the increase in the breath and fecal 14C soon after the bypass is only moderate, then that suggests an inadequate bypass.